A neutron and gamma ray integrated aluminum-based nuclear shielding material and preparation method thereof
By using high-entropy alloys as gamma ray shielding components in aluminum-based nuclear shielding materials, combined with the preparation method of boron carbide and aluminum alloy, the problem of low shielding efficiency in the prior art is solved, efficient shielding of gamma rays is achieved, and suitable for small modular nuclear reactors.
Patent Information
- Application Number
- CN202411658309.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The shielding efficiency of existing nuclear reactor shielding materials is low, making it difficult to meet the requirements of small modular nuclear reactors for nuclear shielding materials.
A high-entropy alloy is used as the shielding component of gamma rays, combined with boron carbide and aluminum alloy, and aluminum base core shielding materials are prepared through ball milling, cold pressing, hot press sintering, hot rolling and solid solution aging heat treatment.
It significantly improves the shielding efficiency of aluminum-based nuclear shielding materials to gamma rays, and is suitable for small modular nuclear reactors, while maintaining good mechanical properties and plastic deformation capabilities.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nuclear materials, and in particular relates to a neutron and gamma ray integrated aluminum-based nuclear shielding material and a preparation method thereof. Background Art
[0002] The modularization of nuclear reactors has significantly limited their weight and volume, placing higher demands on reactor shielding materials. Nuclear reactors are primarily exposed to neutron and gamma-ray radiation during operation. Current shielding materials used in China, such as lead-boron polyethylene and boron steel, are unable to meet these requirements due to insufficient structural strength and low shielding efficiency. Therefore, there is an urgent need to optimize the composition and preparation processes of existing shielding materials, improve and enhance their shielding performance while maintaining structural mechanical properties, reduce overall costs, expand their application areas, and advance industrialization.
[0003] To ensure that shielding materials possess the dual function of shielding both neutrons and gamma rays, it is necessary to increase the content of neutron-shielding components such as Cd, B, and Gd within the composite shielding material to enhance its neutron shielding performance. Furthermore, it is necessary to significantly increase the proportion of heavy metal elements to improve the material's gamma-ray shielding performance. Aluminum-based composites are currently widely used in various fields of industry and life. Among them, aluminum-based boron carbide composites, with their outstanding advantages such as light weight, high strength, excellent corrosion resistance, high thermal conductivity, and stable neutron absorption, have been widely used in the storage and transportation of spent fuel. Introducing gamma-ray shielding components into aluminum-based boron carbide composites can impart both neutron and gamma-ray shielding properties.
[0004] The Chinese invention patent "Aluminum-based composite material for shielding high-dose gamma rays and thermal neutrons and its preparation method" (Publication No. CN109402477B) achieves shielding effects against high-dose gamma rays and thermal neutrons by adding 75% to 90% tungsten and 0.5% to 3% boron to the aluminum-based composite material. The Chinese invention patent "Aluminum-based composite material for nuclear reactors shielding neutrons and gamma rays and its preparation method" (Publication No. CN105803267B) utilizes isostatic pressing to develop an aluminum-based composite material with sufficient mechanical strength and excellent resistance to neutron and gamma ray radiation from nuclear reactors. This aluminum-based composite material comprises 20% to 70% tungsten and 1% to 10% boron carbide. However, both of these patents use tungsten as the gamma-ray shielding component, which has low shielding efficiency and is difficult to meet the requirements of nuclear shielding materials for small modular nuclear reactors. Summary of the Invention
[0005] The present invention aims to overcome the shortcomings of the prior art by providing an integrated aluminum-based nuclear shielding material for neutrons and gamma rays. By incorporating a high-entropy alloy as a gamma-ray shielding component, this aluminum-based nuclear shielding material effectively improves its gamma-ray shielding efficiency, making it suitable for modular nuclear reactors. This addresses the problem of conventional shielding materials having low shielding efficiency and their inability to meet the requirements of small modular nuclear reactors.
[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a neutron and gamma-ray integrated aluminum-based nuclear shielding material, characterized in that the aluminum-based nuclear shielding material includes the following components in mass percentage: 1%~10% boron carbide, 5%~30% high entropy alloy powder, and 60%~94% aluminum alloy powder.
[0007] The above-mentioned neutron and gamma-ray integrated aluminum-based nuclear shielding material is characterized in that the high entropy alloy powder is one of TiZrNbTa, TiZrNbHf and TiZrNbTaHf, and the aluminum alloy powder is one of 2 series aluminum alloy powder, 5 series aluminum alloy powder, 6 series aluminum alloy powder and 7 series aluminum alloy powder.
[0008] The present invention adopts one of TiZrNbTa, TiZrNbHf and TiZrNbTaHf as the raw material of the aluminum-based nuclear shielding material. Since the above-mentioned high-entropy alloy has high strength, hardness and plasticity, it will not cause a significant decrease in the plasticity of the material when added as second-phase particles to the aluminum matrix; in addition, the elements contained in the above-mentioned high-entropy alloy are all elements with high density, which is beneficial to improving the shielding performance of the aluminum-based nuclear shielding material against gamma rays.
[0009] The above-mentioned neutron and gamma-ray integrated aluminum-based nuclear shielding material is characterized in that the average particle size of the high entropy alloy powder is 10μm~100μm.
[0010] By setting the particle size of the high-entropy alloy powder to 10 μm to 100 μm, the present invention can avoid the difficulty in uniform dispersion and easy agglomeration of the high-entropy alloy powder when the particle size is less than 10 μm; and avoid the tendency of cracks in the prepared aluminum-based nuclear shielding material during the stretching process when the high-entropy alloy powder is larger than 100 μm, thereby reducing the mechanical properties of the aluminum-based nuclear shielding material.
[0011] In addition, the present invention also discloses a method for preparing the above-mentioned neutron and gamma-ray integrated aluminum-based nuclear shielding material, which is characterized in that the preparation method comprises the following steps:
[0012] Step 1: boron carbide, high entropy alloy powder and aluminum alloy powder are mixed and ball-milled to obtain a powder;
[0013] Step 2: drying the powder obtained in step 1 and then crushing it;
[0014] Step 3: cold pressing and hot pressing the powdered material crushed in step 2 to obtain a composite material ingot;
[0015] Step 4: hot rolling and solution aging heat treatment are performed on the composite material ingot obtained in step 3 to obtain an aluminum-based nuclear shielding material.
[0016] The above-mentioned method for preparing an integrated aluminum-based nuclear shielding material for neutrons and gamma rays is characterized in that the rotation speed of the ball mill in step one is 100r / min~350r / min, the time of the ball milling is 1h~7h, and the ball-to-material ratio of the ball milling is 10:1~20:1.
[0017] The above-mentioned method for preparing a neutron and gamma-ray integrated aluminum-based nuclear shielding material is characterized in that the drying time in step 2 is 12 hours to 24 hours.
[0018] The above-mentioned method for preparing the integrated neutron and gamma-ray aluminum-based nuclear shielding material is characterized in that the cold pressing pressure in step three is 200MPa~300MPa.
[0019] The present invention can avoid the situation where the pressure is too low and is not conducive to powder molding by setting the cold pressing pressure to 200MPa-300MPa, and when the pressure exceeds 300MPa, further increasing the pressure will not significantly increase the density of the material.
[0020] The above-mentioned method for preparing an integrated aluminum-based nuclear shielding material for neutrons and gamma rays is characterized in that the temperature of the hot pressing sintering in step three is 550°C~620°C, the pressure of the hot pressing sintering is 20MPa~50MPa, and the holding time of the hot pressing sintering is 10min~60min.
[0021] The present invention sets the hot pressing sintering temperature at 550°C to 620°C. Since the melting point of aluminum alloy is about 660°C, the aluminum alloy will melt when the sintering temperature is too high, while it is difficult to form a sintering neck when the temperature is too low, which is not conducive to the densification of the material. The hot pressing sintering pressure is set at 20MPa to 50MPa to avoid difficulty in ensuring the density of the material when the pressure is lower than 20MPa. When the pressure is higher than 50MPa, the density of the material will not increase significantly with the increase of pressure.
[0022] The above-mentioned method for preparing an integrated aluminum-based nuclear shielding material for neutrons and gamma rays is characterized in that the hot rolling temperature in step four is 350°C~500°C, the total deformation of the hot rolling is 50%~90%, and the deformation of each pass of the hot rolling is 5%~15%.
[0023] The present invention can eliminate defects such as pores inside the material by hot rolling, further improving the density of the material. By setting the hot rolling temperature at 350°C to 500°C, it can avoid the material's deformation resistance being large due to the rolling temperature being too low, and the material melting when the temperature is too high. By controlling the total deformation amount and the deformation amount per pass, the material can be fully deformed and the cracking of the material can be reduced.
[0024] The above-mentioned method for preparing a neutron and gamma-ray integrated aluminum-based nuclear shielding material is characterized in that the solution temperature of the solid solution aging heat treatment in step 4 is 525°C~540°C, the solution time of the solid solution aging heat treatment is 30min~120min, the aging temperature of the solid solution aging heat treatment is 160°C~180°C, and the aging time of the solid solution aging heat treatment is 6h~10h.
[0025] The present invention utilizes a solution-aging heat treatment to fully dissolve the alloying elements within the aluminum alloy powder into the aluminum matrix to form a supersaturated solid solution. This then slowly precipitates the dispersed nano-reinforcement phase within the supersaturated solid solution, resulting in lattice distortion and significantly improving the strength and hardness of the aluminum alloy. By controlling the temperature and time at each stage of the solution-aging heat treatment, the alloying elements are fully dissolved, grain growth is prevented, and a large number of dispersed nano-precipitated phases are precipitated within the aluminum matrix. For example, during the solution treatment of a 6-series aluminum alloy powder, the Mg2Si phase is fully dissolved within the matrix, forming a supersaturated solid solution and enhancing the material's strength and hardness.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] 1. By adopting high entropy alloy as the gamma-ray shielding component, the present invention can utilize the lattice distortion brought about by the multi-principal element effect of the high entropy alloy to shorten the range of photons in the aluminum-based nuclear shielding material, thereby improving the shielding efficiency of the aluminum-based nuclear shielding material against gamma rays; compared with aluminum-based shielding materials of the same volume or mass using tungsten as the shielding component, the aluminum-based nuclear shielding material of the present invention has higher shielding efficiency and is suitable for application in small modular reactors.
[0028] 2. In the present invention, the high entropy alloy is preferably a titanium-based high entropy alloy. The titanium-based high entropy alloy has a body-centered cubic structure, has high strength, hardness and relatively ideal plasticity. Adding the titanium-based high entropy alloy to the aluminum-based nuclear shielding material can serve as a reinforcing phase to enhance the strength, while having no significant effect on the plasticity of the aluminum-based nuclear shielding material.
[0029] 3. The present invention adopts titanium-based high-entropy alloy instead of tungsten as the gamma-ray shielding component. Since the plasticity of titanium-based high-entropy alloy is better than that of tungsten, the prepared aluminum-based nuclear shielding material has excellent plastic deformation ability, and it is not easy to produce cracks on the surface during subsequent extrusion, rolling and other processes, avoiding the phenomenon of cracking of existing aluminum-based nuclear shielding materials during plastic deformation.
[0030] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the microstructure diagram of the aluminum-based nuclear shielding material prepared in Example 1 of the present invention.
[0032] Figure 2 This is a graph showing the tensile stress-strain test results of the aluminum-based nuclear shielding material prepared in Example 1 of the present invention.
[0033] Figure 3 The aluminum-based nuclear shielding material prepared in Example 1 of the present invention is Co 60 Ray shielding rate test chart. DETAILED DESCRIPTION
[0034] The aluminum-based nuclear shielding material of this embodiment is composed of the following components in percentage by mass: 3% boron carbide, 10% TiZrNbTa and 87% Al6061 powder, wherein the average particle size of TiZrNbTa is 25 μm.
[0035] The preparation method of the aluminum-based nuclear shielding material of this embodiment includes the following steps:
[0036] Step 1: Boron carbide, TiZrNbTa and Al6061 powders were mixed and placed in a planetary ball mill, and ball milled at a speed of 200 r / min for 5 hours to obtain a powder; the ball-to-powder ratio was 10:1;
[0037] Step 2: Dry the powder obtained in step 1 for 12 hours and then crush it;
[0038] Step 3: placing the powder crushed in Step 2 into a steel mold for cold pressing at a pressure of 200 MPa, and then transferring it into a graphite mold for hot pressing and sintering at a temperature of 580°C and a pressure of 35 MPa to obtain a composite material ingot; the hot pressing and sintering holding time is 30 minutes;
[0039] Step 4. Hot rolling the composite material ingot obtained in step 3 at a rolling temperature of 450°C, and then performing solid solution aging heat treatment to obtain an aluminum-based nuclear shielding material; the total deformation of the hot rolling is 50%, the deformation of each hot rolling pass is 5%, the solid solution temperature of the solid solution aging heat treatment is 535°C, the solid solution time is 90min, the aging temperature is 175°C, and the aging time is 8h.
[0040] The TiZrNbTa in this embodiment can be replaced by TiZrNbHf or TiZrNbTaHf, and the Al6061 powder can be replaced by one of the 2-series aluminum alloy powder, 5-series aluminum alloy powder and 7-series aluminum alloy powder other than Al6061 powder.
[0041] The microstructure of the aluminum-based nuclear shielding material prepared in this embodiment was observed. Figure 1 As shown, boron carbide and TiZrNbTa are uniformly distributed in the aluminum-based core shielding material.
[0042] The aluminum-based nuclear shielding material prepared in this embodiment was subjected to a tensile stress-strain test, with a thickness of 30 mm as the sample. The results are as follows: Figure 2 As shown, the tensile strength of the aluminum-based nuclear shielding material is 420 MPa and the elongation is 4%, indicating that the aluminum-based nuclear shielding material has good mechanical properties.
[0043] The aluminum-based nuclear shielding material prepared in this embodiment was subjected to γ-ray (Co 60 The shielding rate test of the ray) is as follows Figure 3 As shown, the aluminum-based nuclear shielding material has a great impact on Co 60 The shielding rate of the radiation increases with the increase of the material thickness. When the thickness of the aluminum-based nuclear shielding material reaches 30mm, the shielding rate is greater than 30%, indicating that the aluminum-based nuclear shielding material has excellent Co 60 Radiation shielding performance.
[0044] Example 2
[0045] The aluminum-based nuclear shielding material of this embodiment is composed of the following components in percentage by mass: 5% boron carbide, 5% TiZrNbTa and 90% Al2024 powder, wherein the average particle size of TiZrNbTa is 10 μm.
[0046] The preparation method of the aluminum-based nuclear shielding material of this embodiment includes the following steps:
[0047] Step 1: Boron carbide, TiZrNbTa and Al2024 powders were mixed and placed in a planetary ball mill, and ball milled at a speed of 100 r / min for 1 hour to obtain a powder; the ball-to-powder ratio was 15:1;
[0048] Step 2: Dry the powder obtained in step 1 for 18 hours and then crush it;
[0049] Step 3: placing the powder crushed in Step 2 into a steel mold for cold pressing at a pressure of 300 MPa, and then transferring it into a graphite mold for hot pressing and sintering at a temperature of 550°C and a pressure of 35 MPa to obtain a composite material ingot; the hot pressing and sintering holding time is 30 minutes;
[0050] Step 4. Hot rolling the composite material ingot obtained in step 3 at a rolling temperature of 350°C, and then performing solid solution aging heat treatment to obtain an aluminum-based nuclear shielding material; the total deformation of the hot rolling is 70%, the deformation of each hot rolling pass is 10%, the solid solution temperature of the solid solution aging heat treatment is 525°C, the solid solution time is 30min, the aging temperature is 160°C, and the aging time is 6h.
[0051] In this embodiment, the Al2024 powder may also be replaced by one of the 5-series aluminum alloy powder, 6-series aluminum alloy powder and 7-series aluminum alloy powder other than the Al2024 powder.
[0052] Example 3
[0053] The aluminum-based nuclear shielding material of this embodiment is composed of the following components in percentage by mass: 1% boron carbide, 5% TiZrNbHf, and 94% Al5085 powder, wherein the average particle size of TiZrNbHf is 100 μm.
[0054] The preparation method of the aluminum-based nuclear shielding material of this embodiment includes the following steps:
[0055] Step 1: Boron carbide, TiZrNbHf and Al5085 powders were mixed and placed in a planetary ball mill, and ball milled at a speed of 350 r / min for 7 hours to obtain a powder; the ball-to-powder ratio was 20:1;
[0056] Step 2: Dry the powder obtained in step 1 for 24 hours and then crush it;
[0057] Step 3: placing the powder crushed in Step 2 into a steel mold for cold pressing at a pressure of 250 MPa, and then transferring it into a graphite mold for hot pressing and sintering at a temperature of 550°C and a pressure of 20 MPa to obtain a composite material ingot; the hot pressing and sintering holding time is 10 minutes;
[0058] Step 4. Hot rolling the composite material ingot obtained in step 3 at a rolling temperature of 500°C, and then performing solid solution aging heat treatment to obtain an aluminum-based nuclear shielding material; the total deformation of the hot rolling is 90%, the deformation of each hot rolling pass is 15%, the solid solution temperature of the solid solution aging heat treatment is 540°C, the solid solution time is 120min, the aging temperature is 180°C, and the aging time is 10h.
[0059] In this embodiment, the Al5085 powder may be replaced by one of the 2-series aluminum alloy powder, 6-series aluminum alloy powder, and 7-series aluminum alloy powder other than the Al5085 powder.
[0060] Example 4
[0061] The aluminum-based nuclear shielding material of this embodiment is composed of the following components in percentage by mass: 10% boron carbide, 15% TiZrNbTaHf and 75% Al7075 powder, wherein the average particle size of TiZrNbTaHf is 50 μm.
[0062] The preparation method of the aluminum-based nuclear shielding material of this embodiment includes the following steps:
[0063] Step 1: Boron carbide, TiZrNbTaHf and Al7075 powders were mixed and placed in a planetary ball mill, and ball milled at a speed of 250 r / min for 3 hours to obtain a powder; the ball-to-powder ratio was 10:1;
[0064] Step 2: Dry the powder obtained in step 1 for 12 hours and then crush it;
[0065] Step 3: placing the powder crushed in Step 2 into a steel mold for cold pressing at a pressure of 300 MPa, and then transferring it into a graphite mold for hot pressing and sintering at a temperature of 620°C and a pressure of 50 MPa to obtain a composite material ingot; the hot pressing and sintering holding time is 60 minutes;
[0066] Step 4. Hot rolling the composite material ingot obtained in step 3 at a rolling temperature of 400°C, and then performing solid solution aging heat treatment to obtain an aluminum-based nuclear shielding material; the total deformation of the hot rolling is 80%, the deformation of each hot rolling pass is 10%, the solid solution temperature of the solid solution aging heat treatment is 530°C, the solid solution time is 60min, the aging temperature is 170°C, and the aging time is 8h.
[0067] In this embodiment, the Al7075 powder may be replaced by one of the 2-series aluminum alloy powder, 5-series aluminum alloy powder and 6-series aluminum alloy powder other than the Al7075 powder.
[0068] Example 5
[0069] The aluminum-based nuclear shielding material of this embodiment is composed of the following components in percentage by mass: 10% boron carbide, 30% TiZrNbTaHf, and 60% Al6061 powder, wherein the average particle size of TiZrNbTaHf is 10 μm.
[0070] The preparation method of the aluminum-based nuclear shielding material of this embodiment includes the following steps:
[0071] Step 1: Boron carbide, TiZrNbTaHf and Al6061 powders were mixed and placed in a planetary ball mill, and ball milled at a speed of 200 r / min for 5 hours to obtain a powder; the ball-to-powder ratio was 10:1;
[0072] Step 2: Dry the powder obtained in step 1 for 12 hours and then crush it;
[0073] Step 3: The powder obtained from the crushing step 2 is placed in a steel mold for cold pressing at a pressure of 200 MPa, and then transferred to a graphite mold for hot pressing and sintering at a temperature of 600°C and a pressure of 45 MPa to obtain a composite material ingot; the hot pressing and sintering time is 35 minutes;
[0074] Step 4. Hot rolling the composite material ingot obtained in step 3 at a rolling temperature of 450°C, and then performing solid solution aging heat treatment to obtain an aluminum-based nuclear shielding material; the total deformation of the hot rolling is 80%, the deformation of each hot rolling pass is 10%, the solid solution temperature of the solid solution aging heat treatment is 535°C, the time is 90min, the aging temperature is 175°C, and the time is 8h.
[0075] The aluminum-based nuclear shielding materials prepared in Examples 1 to 5 were tested for mechanical properties, thermal neutron (neutron with energy of 0.025 eV) shielding properties and gamma ray (Co 60 ) Shielding performance test, the test results are shown in Table 1.
[0076] Table 1 Performance test results of aluminum-based nuclear shielding materials prepared in Examples 1 to 5
[0077]
[0078] As can be seen from Table 1, the tensile strength of the aluminum-based nuclear shielding materials prepared in Examples 1 to 5 is not less than 405 MPa, and the elongation is not less than 3.5%; when the thickness of the aluminum-based nuclear shielding material is 30 mm, the thermal neutron shielding rate is not less than 99.63%, and the gamma-ray shielding rate is not less than 32.16%; in summary, the aluminum-based nuclear shielding material prepared by the present invention has good mechanical properties and excellent thermal neutron and gamma-ray shielding performance, which meets the performance requirements of shielding materials in fields such as small reactors, mobile reactors and nuclear-powered submarines.
[0079] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention shall still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A neutron and gamma ray integrated aluminum-based nuclear shielding material, characterized in that: The aluminum-based nuclear shielding material is composed of the following components in mass percentage: 1% to 10% boron carbide, 5% to 30% titanium-based high entropy alloy powder, and 60% to 94% aluminum alloy powder, wherein the titanium-based high entropy alloy powder is TiZrNbTa or TiZrNbHf; the aluminum-based nuclear shielding material is prepared by the following method: Step 1: mixing boron carbide, titanium-based high entropy alloy powder and aluminum alloy powder and then ball milling to obtain powder; Step 2, drying the powder obtained in step 1 and then crushing it; Step 3: cold pressing and hot pressing the powder material crushed in step 2 to obtain a composite material ingot; Step 4: hot rolling and solution aging heat treatment are performed on the composite material ingot obtained in step 3 to obtain an aluminum-based nuclear shielding material; the hot rolling temperature is 350°C to 500°C, the total deformation of the hot rolling is 50% to 90%, and the deformation of each hot rolling is 5% to 15%.
2. The neutron and gamma ray integrated aluminum-based nuclear shielding material according to claim 1, characterized in that: The aluminum alloy powder is one of 2 series aluminum alloy powder, 5 series aluminum alloy powder, 6 series aluminum alloy powder and 7 series aluminum alloy powder.
3. The neutron and gamma ray integrated aluminum-based nuclear shielding material according to claim 1, characterized in that: The average particle size of the titanium-based high entropy alloy powder is 10 μm to 100 μm.
4. The neutron and gamma ray integrated aluminum-based nuclear shielding material according to claim 1, characterized in that: The rotation speed of the ball mill in step 1 is 100 r / min~350 r / min, the time of the ball milling is 1h~7h, and the ball-to-material ratio of the ball milling is 10:1~20:
1.
5. The neutron and gamma ray integrated aluminum-based nuclear shielding material according to claim 1, characterized in that: The drying time in step 2 is 12h~24h.
6. The neutron and gamma ray integrated aluminum-based nuclear shielding material according to claim 1, characterized in that: The cold pressing pressure in step 3 is 200MPa~300MPa.
7. The neutron and gamma ray integrated aluminum-based nuclear shielding material according to claim 1, characterized in that: The temperature of the hot pressing sintering in step 3 is 550° C. to 620° C., the pressure of the hot pressing sintering is 20 MPa to 50 MPa, and the holding time of the hot pressing sintering is 10 min to 60 min.
8. The neutron and gamma ray integrated aluminum-based nuclear shielding material according to claim 1, characterized in that: The solution temperature of the solution aging heat treatment in step 4 is 525°C~540°C, the solution time of the solution aging heat treatment is 30min~120min, the aging temperature of the solution aging heat treatment is 160°C~180°C, and the aging time of the solution aging heat treatment is 6h~10h.
Citation Information
Patent Citations
Aluminum matrix composite material for nuclear reactor shielding neutrons and gamma rays and preparation method thereof
CN105803267B
Aluminum-based composite materials for shielding high-dose gamma rays and thermal neutrons and their preparation methods
CN109402477B
Application method of structure and function integrated neutron absorber material
CN109825743A